"For whom the bell tolls"? A 'vulnerability-responsibility' model based on democratic and 'dignified' transactions". (June 2023) - Mitra, Subrata
The welfare state, once seen as the best institutional response to people in need, has steadily come under pressure, as much from shrinking state capacities as from neo-liberal advocates of individual responsibility. Still, despite decline of the post-war consensus on the efficacy of the welfare state, social 'vulnerability' still remains the key focus of public policy. However, though much in use in contemporary political discourse, the logical and practical implications of social vulnerability remain unclear. Its essential subjectivity – it is the 'feeling of vulnerability' which makes one vulnerable – turns the concept into a catch-all variable, impeding rigorous theoretical and empirical analysis. I respond to this problem with a 'vulnerability-responsibility', model. Its parameters include a 'responsive' state, an active civil society and a participatory political environment, bolstered by the assertion of agency of the vulnerable. With India as an empirical exemplar, the essay shows how 'nested' vulnerability – a community of pro-active citizens in need of urgent and vital assistance - in the backdrop of a responsive state and competitive, robust and resilient political participation, can generate a sustainable, context-relevant process to cope with the problem of social vulnerability. The model, currently aimed at vulnerable citizens in a democratic state, has the potential of being extended to non-democracies as well as vulnerable non-citizens into its domain.